2006
DOI: 10.1111/j.1462-2920.2006.01204.x
|View full text |Cite|
|
Sign up to set email alerts
|

Opportunism of Conidiobolus obscurus stems from depression of infection in situ to progeny colonies of host alatae as disseminators of the aphid‐pathogenic fungus

Abstract: Conidiobolus (Entomophthorales: Ancylistaceae) includes common aphid pathogens but causes sporadic mycosis worldwide. This epizootiological opportunism was explored herein by examining the potential of mycosis transmission in the progeny colonies of 513 Myzus persicae alates as disseminators of C. obscurus often infecting aphids. The alates exposed to spore showers were flown for 2.05 (0.01-8.95) km on flight mills and then reared individually on cabbage at 20-23 degrees C for 14 day colonization. All truly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As a life strategy, fungal pathogens form resting spores to survive in situ for the forthcoming host absence, as shown in this study, or spread to where host is available. The alatae infected by Entomophthorales, irrespective of obligate or non-obligate and of forming or not forming RS, have proven to spread with aphid dispersal flight and to establish infection sites in colonized cohorts Chen and Feng, 2006;Zhang et al, 2007;. The lower temperatures of 15-20°C and the longer day lengths of 12-16 h found to enhance the proportions of aphid cadavers forming RS at lower spore concentrations in this study fall in optimal ranges for most of fungus-aphid interactions and are well in accordance with the features of growing seasons which are synchronized with aphid epizootics in the field (Wilding and Perry, 1980;Feng et al, 1991;McLeod et al, 1998;Hatting et al, 2000;Nielsen et al, 2001;Nielsen and Hajek, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a life strategy, fungal pathogens form resting spores to survive in situ for the forthcoming host absence, as shown in this study, or spread to where host is available. The alatae infected by Entomophthorales, irrespective of obligate or non-obligate and of forming or not forming RS, have proven to spread with aphid dispersal flight and to establish infection sites in colonized cohorts Chen and Feng, 2006;Zhang et al, 2007;. The lower temperatures of 15-20°C and the longer day lengths of 12-16 h found to enhance the proportions of aphid cadavers forming RS at lower spore concentrations in this study fall in optimal ranges for most of fungus-aphid interactions and are well in accordance with the features of growing seasons which are synchronized with aphid epizootics in the field (Wilding and Perry, 1980;Feng et al, 1991;McLeod et al, 1998;Hatting et al, 2000;Nielsen et al, 2001;Nielsen and Hajek, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most aphid-pathogenic Entomophthorales, irrespective of obligate or non-obligate species, may form resting spores (zygospores or azygospores; RS) to survive adversity (e.g., host absence) in their life cycles (Barta and Cagáň , 2006). RS formation in vivo reduces drastically the production of primary conidia, which are discharged from cadavers and infect aphid cohorts where the cadavers are located, and causes interruption of fungal infection cycle (Zhang et al, 2007). Thus, exploring mechanisms involved in the RS formation of the aphid pathogens would help understand the seasonal prevalence of aphid mycoses.…”
Section: Introductionmentioning
confidence: 99%
“…Various species of entomopathogenic fungi have been identified in migratory alate aphids trapped from the air (Chen and Feng 2004a;Feng et al 2007;Huang, et al 2008). Zhang et al (2007) found that the dispersal ability of alate M. persicae that were inoculated with Conidiobolus obscurus (Hall & Dunn) (Zygomycota: Entomophthorales) was not different to uninfected aphids and, following dispersal, infected aphids were able to reproduce and transmit the pathogen to their progeny. Several other species of aphid have been recorded as transmitting entomopathogenic fungi when migrating as alates, including S. avenae, Rhopalosiphum padi (L.) and Schizaphis graminum (Rondani) (Feng et al 2004).…”
Section: Vectoring Of Entomopathogenic Fungimentioning
confidence: 98%
“…This finding is of general importance for deep insights into seasonal prevalence and survival strategy of P. nouryi and possibly related fungal pathogens. Resting spore formation of an insect pathogen implies interruption of infection in situ until new infection cycle begins in the following seasons (Eilenberg and Pell, 2007; Zhang et al ., 2007). In nature, high concentrations of conidia discharged onto host aphid colonies or plants they inhabit are likely to achieve at the time of an epizootic that often produces high‐density mycosed cadavers.…”
mentioning
confidence: 99%